Now you see it, now you don't: Explaining inconsistent evidence on gender stereotyping of newborns. (14th August 2015) - Thielmann, Isabel; Erdfelder, Edgar; Stahlberg, Dagmar
Abstract: Parental gender‐stereotyped perceptions of newborns—particularly their physical characteristics—have been discussed as important determinants of sex role socialization from birth on. However, corresponding empirical evidence is inconclusive. We propose that inconsistent findings on gender‐correlated perceptions are due to whether or not actual physical differences between newborn girls and boys are properly (statistically or experimentally) taken into account. In our study, 55 mother–father pairs rated both their own and two unknown newborns, labeled either female or male. Although we successfully replicated the typical gender‐correlated perceptions of own newborns' physical characteristics, all effects were explainable by actual physical sex differences in length and weight at birth. Similarly, no gender‐specific rating differences emerged as a function of labeled gender of unknown children matched in actual physical characteristics. Altogether, the findings demonstrate the vital importance of considering existing sex differences between newborn girls and boys for drawing valid conclusions on gender stereotyping of newborns.